Neuroprotective effect of modified Wu-Zi-Yan-Zong granule, a traditional Chinese herbal medicine, on CoCl2-induced PC12 cells - Zeng, Ke-Wu; Wang, Xue-Mei; Ko, Hyeonseok; Yang, Hyun Ok (ELSEVIER IRELAND LTD, 2010)
Aim of the study: To investigate the neuroprotective effect of aqueous extract of modified Wu-Zi-Yan-Zong granule (MWG), a traditional Chinese herbal medicine, against CoCl2-induced neurotoxicity in PC12 cells. Materials and methods: Cell viability assay, apoptosis rate assay, ROS detection and mitochondrial membrane potential (MMP) assay were performed. In addition, cytochrome c, caspase-3. PARP and MAPKs were also detected by Western blotting. Results: MWG extract increased viability and suppresses early and middle/late stage apoptosis in a dose-dependent manner in CoCl2-induced PC12 cells. Moreover, MWG extract decreased the level of intracellular reactive oxygen species (ROS), increased MMP, regulated Bcl-2 family protein expression (Bcl-2 and Bcl-XL) and inhibited the release of cytochrome c from the mitochondria. In addition, MWG extract attenuated activation of caspase-3 and poly ADP-ribose polymerase (PARP) and inhibited the phosphorylation of ERK, c-Jun NH2-terminal kinase (JNK) and p38 MAPKs. Conclusions: MWG extract exhibited significant neuroprotective effect on PC12 cells, and this effect may be associated with the suppression of ROS generation and inhibition of mitochondria-mediated caspase and MAPK signaling pathways. (C) 2010 Elsevier Ireland Ltd. All rights reserved.
Keywords: ACTIVATED PROTEIN-KINASE; APOPTOSIS; DEATH; INVOLVEMENT; CASPASE-3